LOCAL KNOWLEDGE IN WATERSHED GOVERNANCE FOR ECOSYSTEM RESTORATION: A CASE STUDY OF THE BATANG GADIS RIVER BASIN IN THE SETTLEMENT LANDSCAPE OF MANDAILING NATAL - Cut Nuraini; Feby Milanie; Abdi Sugiarto; Mohd Nazri Saidon (International Journal on Livable Space, 2025)
The Batang Gadis Watershed in Mandailing Natal faces mounting ecological pressures from environmental degradation, changing land-use patterns, and insufficient community participation in conservation initiatives. To address these challenges, the indigenous ecological wisdom of the Mandailing community presents a culturally appropriate and proven framework for watershed stewardship. This study explores local knowledge systems used in river management and evaluates their contribution to ecosystem restoration. Through a qualitative case study methodology, researchers gathered data  via interviews with community elders, direct observation of practices, and comprehensive documentation of river-centered cultural traditions. The study reveals that traditional practices including as lubuk larangan (sacred fishing prohibition areas), ceremonial rituals (marpangir), and streamside management protocols constitute an integrated ecological governance framework. These customary practices help preserve water quality, safeguard biological diversity, and strengthen community-based resource stewardship. The findings demonstrated that indigenous knowledge systems substantially improve watershed resilience. Incorporating these traditional approaches into official environmental framework offers a context-sensitive, community-driven, and culturally authentic pathway for ecological restoration.